Land reforms in India /edited by A.R. Rajapurohit (New Delhi, 1984)
This book covers the following topics Genesis of agrarian relations in the coastal Karnataka; The political economy of land reforms in India reforms; Reforms to pre-empt change land legislation in Karnataka; Collective and distributive Land reforms in India; Disposal of government Waste Lands for Cultivation to Scheduled castes in Tumkur District, Karnataka; Utilization of Surplus land of India; Working of the Land Tribunals of India etc.
Keywords: Land reform-India